A protocol for randomized controlled trial on early active flexion versus passive flexion mobilization therapy for Spaghetti wrist injuries - Kishore Vellingiri; Ashwath M. Acharya; Anil K. Bhat (Journal of Orthopaedic Surgery and Research)
Abstract Background Spaghetti-wrist injuries representing Zone-5 flexor tendon lacerations remain a major challenge for hand surgeons despite the use of careful and meticulous surgical techniques and appropriate rehabilitation programs. Injuries in these regions can lead to adhesion formation, stiffness, and loss of hand function in view of its delicate and complex anatomy. One of the methods to prevent adhesion is the use of active flexion rehabilitation protocols. Its benefits have been shown in numerous reports on zone-2 injuries. However, there is a paucity of reports for this regime in Zone-5 and Spaghetti-wrist injuries. Methods This study proposes a double-blind, single-center, randomized controlled trial (RCT) to compare the functional results of two rehabilitation methods following the repair of Spaghetti-wrist injuries. This includes the passive or active flexion therapy regime performed over six weeks. After fulfilling the inclusion criteria, adults aged 18–60 who have presented with spaghetti-wrist injuries will be selected. Patients will receive a comprehensive document outlining the study’s purpose, methodology, and follow-up schedule, which will be a part of the informed consent. 44 patients will be immobilized in a plaster slab and assigned equally to the passive or active flexion group. They will be assessed for primary and secondary outcomes, which include Tang’s criteria, independent digital function, sensory assessment, pinch and grip strength, and Michigan Hand Outcome Questionnaire (MCHQ), each at six and 12 weeks, six and 12 months. The study will follow the SPIRIT guidelines. Discussion The proposed RCT compares early active and passive flexion regimes’ functional results in zone-5 flexor tendon injuries. This trial is unique as an active flexion regime was not described earlier in a major comparison study. It will answer the role and possible benefits of a more aggressive early active flexion program. Additionally, the study will give information on patient-reported outcomes and address the incidence of complications in a much longer follow-up of one year. Trial registration details The institute ethics committee approval was confirmed for the study (approval No. IEC – 383/2022), and registration for the Clinical Trial Registry of India was completed (CTRI/2023/03/050721).